ANSWER
![x=(2)/(5);x=-(1)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/786f3j2ggpb45bja4hqy01q6ivl6yeb5uf.png)
Step-by-step explanation
We want to solve the given quadratic equation by using the quadratic formula:
![15x^2-x-2=0](https://img.qammunity.org/2023/formulas/mathematics/college/n272c8gh10szcj6vkcwixiq817dpak9yjb.png)
The quadratic formula is:
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/rxvf73usjbbwyik14knxdemoz21vfz2ufc.png)
where a = coefficient of x²
b = coefficient of x
c = constant
From the given equation, we have that:
![a=15,b=-1,c=-2](https://img.qammunity.org/2023/formulas/mathematics/college/slti4poddfanb1g16xnfxwsuk826tqei9a.png)
Therefore, solving using the quadratic formula, we have:
![\begin{gathered} x=\frac{-(-1)\pm\sqrt[]{(-1)^2-4(15)(-2)}}{2(15)} \\ x=\frac{1\pm\sqrt[]{1+120}}{30} \\ x=\frac{1\pm\sqrt[]{121}}{30}=(1\pm11)/(30) \\ \Rightarrow x=(1+11)/(30);x=(1-11)/(30) \\ \Rightarrow x=(12)/(30);x=(-10)/(30) \\ x=(2)/(5);x=-(1)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b7dzy92st35eo5h4vp3hzitqracaf1gz9y.png)
That is the solution of the quadratic equation.